Fase gametofitica del helecho Llavea cordifolia (Pteridaceae) - Reyes Jaramillo, Irma; Pérez-García, Blanca; Mendoza, Aniceto (Revista de Biología Tropical, 2000)
The development and sexual phase characteristics of Llavea cordifolia, a genus that is monotypic to Mexico, Guatemala and Costa Rica. The spores were collected from Veracruz and Puebla, the culture was in vitro on the basis of gametophyte population growing in petri dishes. Spore germination is of the Vittaria-type, resulting in a uniseriate gametophytic filament of four censo Prothallial development is of the Adiantum-type. The protallus is cordate-spatulate to cordate and reaches sexual maturity in 60-160 days. The gametangia are of the common leptosporangiate-type.